2013
DOI: 10.7448/ias.16.4.18752
|View full text |Cite
|
Sign up to set email alerts
|

HIV prevalence and factors associated with HIV infection among men who have sex with men in Cameroon

Abstract: IntroductionDespite men who have sex with men (MSM) being a key population for HIV programming globally, HIV epidemiologic data on MSM in Central Africa are sparse. We measured HIV and syphilis prevalence and the factors associated with HIV infection among MSM in Cameroon.MethodsTwo hundred and seventy-two and 239 MSM aged ≥18 from Douala and Yaoundé, respectively, were recruited using respondent-driven sampling (RDS) for this cross-sectional surveillance study in 2011. Participants completed a structured ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 39 publications
5
54
3
1
Order By: Relevance
“…They note that the sexual identities adopted by MSM are frequently linked to their sexual behaviours and that being the receptive partner in anal sex was associated with adopting a more openly homosexual social identity, whereas men who reported being the penetrative partner in anal intercourse tended not to associate themselves with labels signifying gay identity [43]. Similar findings have been reported from South Africa [38], Senegal [36] and Cameroon [25].…”
Section: Drivers Of Risk In Msm Local Environmentssupporting
confidence: 76%
See 2 more Smart Citations
“…They note that the sexual identities adopted by MSM are frequently linked to their sexual behaviours and that being the receptive partner in anal sex was associated with adopting a more openly homosexual social identity, whereas men who reported being the penetrative partner in anal intercourse tended not to associate themselves with labels signifying gay identity [43]. Similar findings have been reported from South Africa [38], Senegal [36] and Cameroon [25].…”
Section: Drivers Of Risk In Msm Local Environmentssupporting
confidence: 76%
“…In a cohort study in Senegal, Drame et al [23] report an HIV prevalence of 36 %, while in Togo Ekouevi, Dagnra et al [24] report a prevalence of 19.6 % in a cross sectional study in six cities. And, a recent study in Cameroon found HIV prevalence rates of between 25.5 % and 44.4 % among MSM in two cities [25].…”
Section: The Epidemiology Of Hiv In Msm In Ssamentioning
confidence: 98%
See 1 more Smart Citation
“…This is especially the case in West and Central Africa, where the epidemics appear to be more concentrated among key populations 12,15 . Nigeria has a mixed HIV epidemic including both concentrated epidemics within key populations as well as a more generalized epidemic among reproductive age adults.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have linked HIV/STIs with sexual risk behaviors such as inconsistent condom use for anal intercourse and multiple and concurrent sexual partnerships (22, 25). However, although sexual behavior change is an important consideration for HIV/STIs, the epidemic of HIV among MSM is driven substantially by other factors including the social and structural factors that underlie high risk sexual practices (26).…”
Section: Introductionmentioning
confidence: 99%